The Composition and Distribution of Volatile Organic Compounds in Sediments of the East Taijinar Salt Lake in Northern Qinghai-Tibet Plateau - Lu, Xiaohang; Ma, Zhe; Yi, Lei; Zhang, Guangwu; Chen, Fuhong; Han, Fengqing (Frontiers in Environmental Chemistry, 2021)
The main objective of this study was to explore the composition and distribution of volatile organic compounds (VOCs) and the factors that affect their distribution in the salt lake sediments. Thirteen sediment samples were collected from a depth profile in the East Taijinar Lake, China. VOCs of different samples were extracted by headspace solid phase microextraction. Gas chromatography-ion mobility spectrometry, gas chromatography-mass spectrometry, and X-ray diffraction were used to analyze the VOCs, n-alkanes, and minerals present in samples. Thirty-four VOCs were identified and classified into seven types, including terpenes, furans, esters, aldehydes, ketones, alcohols, and acids, apart from six contaminants. It was found that 24 of the most prevalent compounds in clay were on average 101.45% higher than those in sandstone and halite because of the sedimentary environment, while the remaining ten (2-acetylfuran, 2-pinene D, etc.) were on average 13.27% higher in sandstone and halite sediments than in clay. This can be attributed to their different biological sources, porosity, and higher salinity. Based on the Q-cluster analysis, the 13 sediment samples were split into two groups, including the group according to composition and the group based on distribution of VOCs. In this study, it was found that the VOCs correlate positively with detrital minerals, with Group I exhibiting a high content of detrital minerals (>25%), while Group II showed the opposite characteristics. The consumption of organic matter (OM) by microorganisms leads to the formation of VOCs in sediment. The values of carbon preference index and n-alkane further demonstrate that the OM of the two groups came from different sources, exogenous and endogenous. Pr/Ph ratios, Pr/C17, and Pr/C18 also suggest that the OM in all sediments was strongly affected by microorganisms in an anoxic environment. Together, these results demonstrate that the OM from different biological sources and microbial activities played a critical role in deciding the composition and distribution of VOCs in the sediment. This study also shows that the proportion of VOCs in halite was discernably higher than that in clay and sandstone and that the content of VOCs should be considered when studying OM in salt lake sediments.